Konsekuensi Yuridis Terhadap Diabaikannya Pelaksaan Putusan Pengadilan Tata Usaha Negara Yang Telah Memiliki Kekuatan Hukum Tetap - Saartje Sarah Alfons (SASI, 2018)
Unlawful Consequences of Justice in the execution of the decision of the State Administration court by government officials, are arbitrary and contempt of court actions which may be subject to administrative sanctions as well as unlawful acts that may be sued in civil courts.